Jejunal lipoma: A rare cause of small bowel bleeding - Marko Kozyk; Kateryna Strubchevska; Mihaela Batke (Clinical Case Reports, 2023)
Abstract Prompt endoscopic recognition as well as histopathological examination are crucial for establishing the diagnosis and management of small bowel lipomas complicated by bleeding.